2011
DOI: 10.1001/archinternmed.2011.131
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With β-Blockers and Reduced Disease Progression in Patients With Thick Melanoma

Abstract: Preclinical evidence shows that β-adrenoceptor antagonists (β-blockers) inhibit tumor and metastasis progression in animal models of melanoma. We hypothesized that the use of β-blockers for concomitant diseases is associated with a reduced risk of progression of thick (Breslow thickness >1 mm) malignant melanoma. Two patient subgroups were identified from the medical records of 121 consecutive patients with a thick melanoma. Of these, 30 patients had been prescribed β-blockers for 1 year or more (treated subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 10 publications
10
121
0
3
Order By: Relevance
“…15,16 The use of b-blockers, on the other hand, has been associated with prolonged survival in women treated for breast cancer, [17][18][19][20] as well as in patients affected with prostate, 21,22 lung, 23 ovarian 24 and cutaneous melanoma. 25,26 A commonality among these studies is that the conditions and drugs involved affect the sympathetic nervous system (SNS), whose activity is stimulated by chronic stress and depression and inhibited by b-blockers.…”
Section: Neuroendocrine Factors and Bone Metastasismentioning
confidence: 99%
“…15,16 The use of b-blockers, on the other hand, has been associated with prolonged survival in women treated for breast cancer, [17][18][19][20] as well as in patients affected with prostate, 21,22 lung, 23 ovarian 24 and cutaneous melanoma. 25,26 A commonality among these studies is that the conditions and drugs involved affect the sympathetic nervous system (SNS), whose activity is stimulated by chronic stress and depression and inhibited by b-blockers.…”
Section: Neuroendocrine Factors and Bone Metastasismentioning
confidence: 99%
“…11 In addition, recent evidence suggests a dramatic role of b-AR blockers in reducing metastases, tumour recurrence and specific mortality in breast cancer patients. 12 More recently, the use of b-blockers for concomitant disease was associated with a reduced risk of progression of thick melanoma 13 and with an increased survival time of melanoma patients, 14 suggesting that the interaction of catecholamines with b-ARs could be a useful target in this disease.…”
mentioning
confidence: 99%
“…Indeed, data from many epidemiologic and experimental studies have revealed that the β-adrenergic receptor signaling pathway was involved in the proliferation, metastasis, and angiogenesis of several types of tumors [34][35][36]. Accumulating evidence has indicated that IH is a powerful sympathetic activator [37,38].…”
Section: Discussionmentioning
confidence: 99%